Jezus Chrystus w "Kolędzie" i "Pasterce" Jerzego Lieberta = Jezus Christ in "Carol" [Kolęda] and "Christmas Eve Mass" [Pasterka] by Jerzy Liebert - Jabłoński, Romuald Marek (1956- ) (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Jerzy Liebert (1904-1931) is an outstanding representative of Polish catholic poetry. In his "Carol" and "Christmas Eve Mass" he uses Christmas motifs. The analysis of "Carol" brings a discovery of texts two layers. The first one is the picture of Mother who cares for her Child - this layer is easy to notice. The second one, an announcement of Jesus passion and death, is only indicated by certain poetic words, e.g. allusions to Jan Kochanowski's "Laments" [Treny].
Keywords: Liebert, Jerzy (poeta; 1904-1931); Jezus Chrystus; Boże Narodzenie; Dzieciątko; Matka; kolęda; Jesus Christ; Christmas; Baby Jesus; Mother; carol